Eficiencia energética mediante sistemas scada para el control de la demanda de una residencia - Juna Juca, Edwin Adrian (2015)
This thesis develops a prototype of SCADA system which can be controlled residential loads, the system consists of pluggable equipment to which the load to be monitored is connected. The communication between devices that are part of the system will be using ZigBee communication protocol, protocol very reliable wireless communications. The base operating system is via a demand curve, demand curve that is obtained by mathematical modeling. Mathematical modeling is used Artificial Neural Networks (ANN) modeling that perfectly fits the needs of this project. For forecasting the demand for residential electricity data were taken using a Fluke 43b, of which the mathematical model for forecasting demand is served. Demand values obtained will be compared with a benchmark and as scheduled, the system automatically connect or disconnect the existing loads in the residence. In addition to this thesis project we try to present both economic benefits and environmental benefits that come hand in hand with the use of this new technology.